Effective and responsive government - Regulatory reform initiatives of union government (Note) - Jha, Nikhilesh (1999)
Covering the entire gamut of activities initiated as a follow up of an Action Plan on the subject endorsed by the 1997 Conference of Chief Ministers, the author presents details of regulatory reform measures undertaken at the Union level. He picks up for discussion efforts of Finance Ministry, expert groups, Commission on Review of Administrative Law, Bills on Freedom of Information and Electronic Data Transfer and Transaction, and amendments to related Acts affecting regulatory reforms. - Reproduced
Keywords: Note; Public administration